2018
DOI: 10.1002/oby.22266
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Sleep Quality and Quantity in the Link Between Food Insecurity and Obesity Across Race and Ethnicity

Abstract: Food security and sleep hygiene should be an integral part of the fight against obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…As hypothesized, the present study found that short sleep duration mediated the relationship between financial stress and dietary risk score among students reported short sleep duration. This finding is consistent with the finding from another study, in which it was noted that very short (≤4 h per night) and short sleep (5 to 6 h per night) duration mediated the relationship between food insecurity and obesity [ 67 ]. There are several mechanisms that could plausibly contribute to these relationships.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesized, the present study found that short sleep duration mediated the relationship between financial stress and dietary risk score among students reported short sleep duration. This finding is consistent with the finding from another study, in which it was noted that very short (≤4 h per night) and short sleep (5 to 6 h per night) duration mediated the relationship between food insecurity and obesity [ 67 ]. There are several mechanisms that could plausibly contribute to these relationships.…”
Section: Discussionsupporting
confidence: 92%
“…Based on experimental studies noting the causal relationships between perceived stress and sleep quality as well as with sleep quality and dietary behaviors [ 63 , 64 , 65 , 66 ], the mediation effect of sleep quality on the relationship between financial stress and dietary risk score is plausible. Additionally, one other study explored the mediation effect of sleep quality on the relationship between food insecurity and obesity and revealed that poor sleep quality, specifically trouble falling asleep and maintaining sleep, mediated the relationship between food insecurity and obesity [ 67 ]. Because obesity is associated with undesirable dietary behaviors [ 16 , 17 ], and based on the totality of the evidence, poor sleep quality appears to serve as an intermediate factor that explains the connection between financial stress and dietary risk score.…”
Section: Discussionmentioning
confidence: 99%
“…Another more straightforward explanation is related to the previously mentioned association between food insecurity and mental health issues. The anxiety and stress resulting from food insecurity often triggers sleep loss, all of which can increase the consumption of cheap energy-dense foods, or comfort foods, inducing excessive weight gain (Dallman et al, 2003;FAO et al, 2018;Frongillo, 2013;Narcisse et al, 2018).…”
Section: Food Security and Obesity Pathwaysmentioning
confidence: 99%
“…Additionally, NHPIs experience higher rates of poverty and lower educational attainment than the general US population [19,51]. Population-based studies of NHPIs have documented a correlation between diabetes and diabetes-related risk factors, such as inadequate sleep, poor nutrition or eating habits, food insecurity and obesogenic food environments, and physiological distress, all of which may be consequences of economic instability [52][53][54].…”
Section: Diabetes Disparitiesmentioning
confidence: 99%